1991
DOI: 10.1073/pnas.88.14.6053
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR study of renal trimethylamine responses to dehydration and acute volume loading in man.

Abstract: We have used volume-localized 'H NMR spectroscopy to detect and measure changes in medullary trimethylamines (TMAs) in the human kidney in vivo. Localized water-suppressed 'H spectra were collected from a volume of interest located within the renal medulla by using a stimulated echo-based localization scheme. The principal resonances in the medullary 'H spectrum were residual water (4.7 ppm), lipid (0.9-1.4 ppm), and TMAs (3.25 ppm). The TMA line width was 7-15 Hz before filtering, and the signal-to-noise rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…(12), where betaine and inositol were found to increase in parallel with dehydration, although sorbitol and GPC showed more complicated changes, and with the study of the rabbit kidney by Bagnasco et al (13) where GPC, betaine, inositol, and sorbitol all increased following dehydration. The previous study of human renal function in vivo by Avison et al (3), showed an increase in the TMA resonance following overnight dehydration, which decreased after rehydration, but because of the long echo times used in this study, no other osmolytes were detectable. In both studies, the urine osmolarity reached a minimum at 2 h following rehydration, and this decrease preceded the change in kidney metabolite signals, which was most pronounced at 4 h. We have attempted to assess the contribution of signals from the urine to the kidney spectra.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…(12), where betaine and inositol were found to increase in parallel with dehydration, although sorbitol and GPC showed more complicated changes, and with the study of the rabbit kidney by Bagnasco et al (13) where GPC, betaine, inositol, and sorbitol all increased following dehydration. The previous study of human renal function in vivo by Avison et al (3), showed an increase in the TMA resonance following overnight dehydration, which decreased after rehydration, but because of the long echo times used in this study, no other osmolytes were detectable. In both studies, the urine osmolarity reached a minimum at 2 h following rehydration, and this decrease preceded the change in kidney metabolite signals, which was most pronounced at 4 h. We have attempted to assess the contribution of signals from the urine to the kidney spectra.…”
Section: Discussionmentioning
confidence: 50%
“…The relative amounts of the various metabolites could not be quantified due to the overlap of the signals in this region and the uncertainty of the assignments. Previous studies of the human kidney in vivo by Avison et al (3) and by Shah et 01. (4) detected in this region only the TMA resonance at 3.25 ppm.…”
Section: Discussionmentioning
confidence: 96%
“…The TMA methyl resonance found at ∼3.3 ppm in vivo primarily represents the osmolytes betaine and glycerophosphorylcholine. Osmolyte levels fluctuate with the degree of kidney‐tissue hydration (31, 32). Collecting kidney MRS spectra in vivo without water suppression is useful, as the amplitude of the water signal can serve to normalize the TMA concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of cardiac and respiratory motion in the brain has made it a productive site for investigation in vivo (23,24). Conversely, investigation of the kidney in vivo has been hampered by respiratory and cardiac motion, although some preliminary studies in humans have been successful (21,25,26).…”
Section: Image-directed Volume Localized Mrs Of the Intact Kidneymentioning
confidence: 97%
“…1 H MRS of the human kidney in vivo has been performed using the stimulated echo acquisition mode (STEAM) sequence and large voxels containing both medulla and cortex in volumes of 27 cm 3 (26) without respiratory gating or 43 cm 3 (25) and 15.6 cm 3 with respiratory gating (21). The spectra contained peaks from lipid and residual water (after water suppression), with localization volumes of 27 cm 3 (26) and 43 cm 3 (25), contained an additional broad peak assigned to the N-methyl protons on the trimethyl- amines, betaine, and GPC. Dixon and Frahm used localization volumes of 15.6 cm 3 and reported that most spectra contained overlapping resonances between 3.5 and 4.1 ppm in addition to the betaine peak (21).…”
Section: Detection and Differentiation Of Cortical And Medullary Osmomentioning
confidence: 99%